Accurate integral counting using multi-channel analyzers. (May 2020) - Fitzgerald, Ryan; King, Lynne
Abstract: Many techniques in radionuclide metrology rely on accurate measurement of the total count rate, that is integral counting, from a detector. We present the design and results from integral counting using a live-timed multi-channel analyzer (MCA) based on a list-mode digitizer and a live-timed scalar, both with imposed, extending dead times. These systems were benchmarked against an existing NIST anti-coincidence counting system. Both systems were used to determine correction factors to an MCA that uses Gedcke-Hale dead-time corrections. Tests were performed for a large-area gas-flow proportional counter and a NaI(Tl) detector for count rates up to 80 000 s −1 . The results were used to create correction factors suitable for alpha- and beta-particle emission rate calibrations. Highlights: Validated simple live-timed counting module with imposed extending dead-time. Created and tested an MCA using a digitizer and imposed extending dead-time. Measured correction factors to Gedcke-Hale-based MCA for integral counting.